Fostering Creativity Through Digital Art Activities in ScratchJr for Kindergarten in Indonesia - Widya Dwi Hardiyanti; Prayitno Prayitno; Puteri Annisa Tsamrotul Fuadah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the process of digital art activities through ScratchJr to develop creativity in early childhood. This study uses a qualitative approach with children aged 5-6 years at Nur Hidayah IT Kindergarten Surakarta. Data collection was carried out through documentation, observation, and interviews. Data analysis uses the qualitative descriptive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing or verification. The results of this study suggest that digital art activities, such as those facilitated by ScratchJr, can encourage children to think imaginatively through a simple coding process that is both creative and fun, leveraging technology. Based on the results of interviews with children's teachers who are allowed to learn using technology more enthusiastically, imagination games such as ScratchJr can provide opportunities to think creatively, and children can freely express themselves with their creativity to make animations. Digital art activities through ScratchJr are recommended for early childhood learning, so that children can gain learning experiences using digital technology and stimulate creativity as a provision for the future.